2016
DOI: 10.1007/s10067-016-3389-4
|View full text |Cite
|
Sign up to set email alerts
|

Professional ballet dancers have a similar prevalence of articular cartilage defects compared to age- and sex-matched non-dancing athletes

Abstract: Ballet exposes the hip joint to repetitive loading in extreme ranges of movement and may predispose a dancer to pain and osteoarthritis (OA). The aims of this study were to compare the prevalence of cartilage defects in professional ballet dancers and athletes and to determine the relationship of clinical signs and symptoms. Forty-nine male and female, current and retired professional ballet dancers and 49 age- and sex-matched non-dancing athletes completed hip pain questionnaires, including the Copenhagen Hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…Three studies (627 participants, 1237 hips) investigated the prevalence of hip OA in asymptomatic athletes using X-ray [54,49,60]. Four studies (40 hips) [65,52,66,67] investigated the prevalence of intra-articular hip pathologies in symptomatic athletes with MRI.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies (627 participants, 1237 hips) investigated the prevalence of hip OA in asymptomatic athletes using X-ray [54,49,60]. Four studies (40 hips) [65,52,66,67] investigated the prevalence of intra-articular hip pathologies in symptomatic athletes with MRI.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In total, 375 (28%) of the athletes were women and 960 were men. The included studies investigated different sports including American football (n=174) [62,49], soccer (n=100) [57,53], ice hockey (n=179) [64,58,59,48], ballet (n=110) [65,52,66,50,63], rugby (n=20) [55], golf (n=55) [67], skiing (n=27) [58], track and field (n=22) [56], capoeira (n=24) [51] and mixed sports (n=624) [65,52,66,61,54,60]. The level of play reported in the included studies included professional [63,65,52,66,50,59,64,61], elite [56,48,67,55,54,49,62,59], semi-professional [57], amateur or recreational [57,65,52,66,61] and youth/high school level…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies (two HR)48 54 reported cartilage defect prevalence per person in ice hockey players (18%)48 and high school athletes (8%) 54. Moderate evidence of a pooled cartilage defect prevalence of 33% (95% CI 16% to 56%) per hip was demonstrated from two studies (one MR and one LR)51 65 using MRI (online supplementary appendix 3 figure 2). One study (HR)54 reported a cartilage defect prevalence per hip of 4%.…”
Section: Resultsmentioning
confidence: 98%